Composite membrane as well as preparation method and application thereof
By growing the metal organic frame in situ on the polylactic acid film and forming a composite film, the trade-off problem between permeability and selectivity of the existing membrane separation technology is solved, and a composite film with high permeability and excellent oil-water separation performance is achieved.
Patent Information
- Application Number
- CN202510661928.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-22
- Publication Date
- 2025-06-20
- Estimated Expiration
- 2045-05-22
AI Technical Summary
The existing membrane separation technology is difficult to balance between achieving high permeability and high selectivity, and the metal organic frame (MOF) film has low catalytic activity and is difficult to process into dense defect-free films.
The polylactic acid film is soaked in an alkaline solution and then placed in a metal organic frame reaction solution for growth in situ to form a composite film. This method increases the roughness and active groups on the membrane surface through alkaline hydrolysis reaction, and promotes uniform coverage and growth of MOF.
The high permeability of the composite membrane and excellent oil-water mixture separation performance are achieved, and the preparation method is simple to operate and low-carbon and environmentally friendly.
Smart Images

Figure CN120169190A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the technical field of membrane separation, and particularly relates to a composite membrane, a preparation method thereof, and an application thereof. Background Art
[0002] Oily wastewater is an important source of global water resource pollution, especially in the case of marine crude oil spills and industrial production processes. Its complex pollutant components pose a serious threat to water quality, biodiversity, and ecosystem functions. In the past decade, significant progress has been made in the basic research and industrial application fields of oily wastewater treatment technologies, especially in the aspects of water environment restoration and waste oil resource recovery. Currently, the treatment methods for oily wastewater mainly include mechanical skimming, air flotation, centrifugation, chemical flocculation, electrocoagulation, and membrane separation technologies, etc. Membrane separation technology has become a key solution to the problem of oily wastewater due to its efficient separation performance and low energy consumption. Although significant progress has been made in membrane research and development, there are still many challenges in achieving rapid and large-scale customized applications. In addition, the inherent trade-off between permeability and selectivity remains the main bottleneck restricting the further development of membrane separation technology. The complexity of the membrane structure and transport mechanism makes it a difficult task to simultaneously achieve high permeability and high selectivity.
[0003] Therefore, there is an urgent need for a comprehensive strategy to address these challenges and optimize the separation performance of the membrane.
[0004] Metal-organic frameworks (MOFs) are porous crystalline materials with high surface areas, pre-designed pore sizes, and uniformly dispersed active sites, which are composed of metal cations or metal clusters and organic ligands. Their rich variety, high porosity, and precise pore structure regulation endow them with customization capabilities, which can be used to achieve precise and high-speed molecular screening for membrane separation. However, existing MOF membranes face many problems, such as low catalytic activity and intercrystalline defects that cannot effectively retain pollutants. In addition, MOFs mainly exist in the form of fine powders or tiny particles, and due to the characteristics of the powders themselves, it is difficult to process them into dense and defect-free membranes through conventional solvent and melt processing technologies.
[0005] Therefore, it is crucial to develop a composite membrane to overcome the above defects. Summary of the Invention
[0006] In view of the above problems, this application provides a composite membrane, a preparation method thereof, and an application thereof. The preparation method of the composite membrane is simple to operate, and the preparation process is low-carbon and environmentally friendly; the composite membrane obtained by the preparation method has high permeability and excellent oil-water mixture separation performance.
[0007] In a first aspect, this application provides a preparation method of a composite membrane, and the preparation method includes the following steps: The polylactic acid film is immersed in an alkaline solution and then placed in a metal organic framework (MOF) reaction solution for in-situ growth to obtain the composite film.
[0008] In the technical solution of the embodiment of the present application, the polylactic acid film is immersed in an alkaline solution, which is used to etch the surface of the polylactic acid film to form a rough surface and active groups, thereby improving the hydrophilicity of the polylactic acid film surface and facilitating the in-situ growth of MOF; specifically, it mainly destroys the ester bonds in polylactic acid (PLA) through an alkaline hydrolysis reaction to form carboxylate groups and alcohols. This chemical change not only increases the hydrophilicity of the PLA surface, but also introduces active carboxyl groups on the surface. These carboxyl groups, as functional active points, can effectively promote the anchoring of the MOF metal center and the nucleation of MOF crystallization; at the same time, the alkali treatment also increases the surface roughness and microporous structure, which provides a larger surface area and more active sites for the uniform coverage and growth of MOF.
[0009] Then it was placed in the metal organic framework reaction solution for in-situ growth. The advantage of NaOH pretreatment is that it significantly improves the hydrophilicity and activity of the PLA membrane surface, which makes it easier for the MOF precursor solution to diffuse and evenly cover the PLA surface, thereby improving the growth efficiency and uniformity of MOF on the PLA surface. In addition, the surface carboxylation enhances the interaction between MOF and the PLA substrate, and improves the stability and durability of the MOF structure by forming a strong coordination bond; the roughened surface structure also provides more active sites and a larger specific surface area for the nucleation and growth of MOF crystals, enhancing the possibility of successful growth of MOF.
[0010] Therefore, the preparation method of the present application is simple to operate, the preparation process is low-carbon and environmentally friendly, and the obtained composite membrane has a large flux, high permeability, and excellent oil-water separation performance.
[0011] In this application, PLA film can be commercially available or homemade, for example, by 3D printing. PLA is derived from renewable resources and has excellent biodegradability, making it an ideal choice for environmentally friendly materials. PLA's low melting point (170-230°C) not only makes the printing process more efficient and energy-saving, but also ensures high printing accuracy. In addition, PLA costs less than ABS and nylon, has outstanding cost-effectiveness, and is suitable for large-scale production and rapid prototyping.
[0012] In some embodiments, the concentration of the alkaline solution is 5 to 15 g / L, such as 6 g / L, 8 g / L, 10 g / L, 12 g / L, 14 g / L, etc.; and / or; The alkali in the alkaline solution includes sodium hydroxide.
[0013] In the technical solution of the embodiment of the present application, the concentration of the alkaline solution is within the above range for the following reasons: A suitable concentration can effectively increase the surface roughness and active groups of the PLA film, thus facilitating the in-situ growth of MOF; if the concentration is too high, it will cause a decrease in the mechanical strength of the PLA film and even breakage, because too strong alkalinity will hydrolyze the ester bonds of PLA excessively, resulting in the breakage of polymer chains; if the concentration is too low, the change in surface roughness will not be obvious, making it difficult for MOF to grow in-situ successfully on the surface of PLA, because there are not enough active groups to promote the nucleation and anchoring of MOF.
[0014] In some embodiments, the temperature of the soaking is 50-70 °C, such as 52 °C, 54 °C, 56 °C, 58 °C, 60 °C, 62 °C, 64 °C, 66 °C, 68 °C, etc.; and / or; the time of the soaking is 20-40 min, such as 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min, etc.
[0015] In the technical solution of the embodiment of the present application, the temperature of the soaking is within the above range for the following reasons: If the temperature is too high, it will cause the rapid bending of the PLA film, making the surface uneven and difficult to form a film; if the temperature is too low, the change in surface roughness will not be obvious, making it difficult for MOF to grow in-situ successfully on the surface of PLA, because there are not enough active groups to promote the nucleation and anchoring of MOF.
[0016] The time of the soaking is within the above range for the following reasons: If the time is too long, it will cause excessive reaction of the PLA material and the weakening of mechanical properties, and even breakage; if the time is too short, the change in surface roughness will not be obvious, making it difficult for MOF to grow in-situ successfully on the surface of PLA, because there are not enough active groups to promote the nucleation and anchoring of MOF.
[0017] In some embodiments, after the soaking, an operation of cleaning the polylactic acid film is further included.
[0018] In the present application, the specific method for cleaning the polylactic acid film is not limited, and the methods well-known in the art can be adopted; as an example, the alkali solution on the surface of the polylactic acid film can be cleaned with water.
[0019] In the present application, the MOF in the metal-organic framework reaction solution can be any one or a combination of at least two of cobalt-based MOF materials, copper-based MOF materials, iron-based MOF materials or zirconium-based MOF materials; optionally, a cobalt-based MOF material is selected.
[0020] In some embodiments, the raw materials for preparing the metal-organic framework reaction solution include 2-aminoterephthalic acid, cobalt-based metal salts and methanol; and / or; The mass ratio of the 2-aminoterephthalic acid to the cobalt-based metal salt is 1:(1.5 - 2.5), where 1.5 - 2.5 can be 1.6, 1.8, 2, 2.2, 2.4, etc.
[0021] In the technical solution of the embodiment of the present application, a combination of 2-aminoterephthalic acid, a cobalt-based metal salt, and methanol is used as a raw material for preparing a metal-organic framework reaction solution. The advantages are as follows: This MOF can be synthesized at room temperature with low energy consumption, and it is a one-pot synthesis method with simple operation and can be prepared on a large scale; the formed metal-organic framework has enhanced hydrophilicity due to the presence of amino groups, which is beneficial for oil-water separation.
[0022] Among them, the mass ratio of the 2-aminoterephthalic acid to the cobalt-based metal salt is within the above range. The reason is that if the mass ratio of the two is too high, it will cause excessive reaction on the surface of the MOF and excessive growth; if the mass ratio of the two is too low, it will be difficult to form crystals or no MOF will be produced, resulting in a failed reaction.
[0023] As an example, the cobalt-based metal salt can be cobalt sulfate heptahydrate.
[0024] As an example, the mass concentration of 2-aminoterephthalic acid in the metal-organic framework reaction solution is 0.1 - 10 g / L, such as 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, etc. It is calculated based on the mass and volume ratio of 2-aminoterephthalic acid to methanol.
[0025] In some embodiments, the method for preparing the metal-organic framework reaction solution includes: mixing 2-aminoterephthalic acid, a cobalt-based metal salt, and methanol, and performing ultrasonic treatment to obtain the metal-organic framework reaction solution; and / or; The time for the ultrasonic treatment is 5 - 6 min, such as 5.2, 5.4, 5.6, 5.8, etc.
[0026] In the technical solution of the embodiment of the present application, the time for the ultrasonic treatment is within the above range. The reason is that if the time is too long, it will cause waste of energy as the solution is already uniform and continuous ultrasonic treatment is unnecessary; if the time is too short, the solution will not be uniform, resulting in slow growth of the MOF.
[0027] In some embodiments, the time for in-situ growth is 24 - 50 h, such as 25 h, 30 h, 35 h, 40 h, 45 h, 50 h, etc.
[0028] As an example, the raw material for preparing the metal-organic framework reaction solution further includes a dispersant, and the dispersant includes polyvinylpyrrolidone.
[0029] In some embodiments, the preparation method includes the following steps: (1) Mix 2-aminoterephthalic acid and cobalt metal salt with methanol, and ultrasonically treat for 5 - 6 min to obtain a metal-organic framework reaction solution; The mass ratio of the 2-aminoterephthalic acid to the cobalt metal salt is 1:(1.5 - 2.5); Immerse the polylactic acid film in an alkaline solution with a concentration of 5 - 15 g / L at 50 - 70 °C for 20 - 30 min, and then wash it; (2) Place the polylactic acid film in the metal-organic framework reaction solution and in-situ grow for 24 - 50 h to obtain the composite film.
[0030] Exemplarily, the method for preparing the composite film of the present application includes the following steps: (1) Prepare a PLA film.
[0031] In the embodiments of the present application, by using a melting-type 3D printer to deposit molten PLA filaments layer by layer, precise control of the film structure and size is achieved. The initial design of the PLA film model is completed using Siemens NX software, and the slicing operation is carried out through Simplify3D software. Subsequently, the sliced model is imported into the 3D printer, and the molten thermoplastic filaments are extruded onto the printing platform through FDM technology (fused deposition modeling technology) to form a strong and uniform film composed of two layers of intertwined filaments layer by layer.
[0032] (2) Pretreat the PLA film with alkali solution.
[0033] In some embodiments of the present application, the PLA film is placed in an alkali solution for pretreatment to achieve the effect of chemical etching and increase the surface roughness.
[0034] Specifically, the concentration of the alkali solution is 5 - 15 g / L, and the treatment time with NaOH can be 20 min - 30 min.
[0035] (3) Prepare the composite film by in-situ growth method.
[0036] In some embodiments of the present application, the metal-organic framework is grown on the surface of the PLA film by the in-situ growth method, and the composite film is prepared by utilizing the interaction between the metal-organic framework and the carboxyl and hydroxyl groups on the PLA film.
[0037] In the second aspect, the present application provides a composite film, which is obtained by the preparation method described in the first aspect; The composite film includes pores, the diameter of the circumscribed circle of the pores is 100 - 250 μm, such as 120 μm, 140 μm, 160 μm, 180 μm, 200 μm, 220 μm, 240 μm, etc.; and / or; The porosity of the composite membrane is 10%-30%, such as 15%, 20%, 25%, etc., and optionally 20%.
[0038] As an example, the shape of the holes includes quasi-circular, circular, regular or irregular polygons (such as triangles, quadrilaterals, pentagons, etc.); as an example, the shape of the holes is rectangular, with a length of 100-200 μm (such as 120 μm, 140 μm, 160 μm, 180 μm, etc.) and a width of 50-150 μm (such as 60 μm, 80 μm, 100 μm, 120 μm, 140 μm, etc.), and optionally the length is 150 μm and the width is 100 μm.
[0039] As an example, by adjusting the extrusion ratio of the extrusion head in fused deposition modeling, the pore size of the composite membrane is adjusted. The extrusion ratio is in the range of 75%-85%, and holes with an outer diameter of 100-250 μm are obtained. For example, when the extrusion ratio is 80%, holes with a length of 150 μm and a width of 100 μm can be obtained; By adjusting the extrusion rate, the porosity of the composite membrane is adjusted. Specifically, the porosity of the composite membrane is equal to 1 - extrusion rate. The extrusion rate is controlled in the range of 70%-90%, and the porosity of the composite membrane is adjusted in the range of 10%-80%.
[0040] In a third aspect, the present application provides an application of the composite membrane described in the second aspect in water purification.
[0041] Compared with the prior art, the present application has at least the following advantages: (1) The preparation method of the present application is simple to operate, and the preparation process is low-carbon and environmentally friendly.
[0042] (2) The composite membrane obtained by the preparation method of the present application has at least high permeability and excellent oil-water mixture separation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] By reading the following detailed description of the preferred embodiments, various other advantages and benefits will become clear to those of ordinary skill in the art. The drawings are only for the purpose of showing the preferred embodiments and are not considered to limit the present application. Moreover, throughout the drawings, the same reference numerals are used to represent the same components. In the drawings: Figure 1 is a process flow chart of the preparation method of the composite membrane for some embodiments; Figure 2 is a scanning electron micrograph of the PLA membrane prepared in Comparative Example 1; Figure 3 is a scanning electron micrograph of the PLA@MOF composite membrane prepared in Example 1; Figure 4 Water contact angle diagrams and underwater oil contact angle diagrams of the PLA@MOF composite membrane prepared in Example 1 and the PLA membrane prepared in Comparative Example 1; Figure 5 Flux test performance diagrams of the PLA@MOF composite membrane prepared in Example 1 and the PLA membrane prepared in Comparative Example 1 for n-hexane oil-water mixtures; Figure 6 Retention performance diagrams of the PLA@MOF composite membrane prepared in Example 1 and the PLA membrane prepared in Comparative Example 1 for n-hexane oil-water mixtures; Figure 7 Results diagrams of retention performance and flux test performance of the PLA@MOF composite membrane prepared in Example 1 and the PLA membrane prepared in Comparative Example 1 for petroleum ether oil-water mixtures; Figure 8 Results diagrams of retention performance and flux test performance of the PLA@MOF composite membrane prepared in Example 1 and the PLA membrane prepared in Comparative Example 1 for n-heptane oil-water mixtures; Figure 9 Results diagrams of retention performance and flux test performance of the PLA@MOF composite membrane prepared in Example 1 and the PLA membrane prepared in Comparative Example 1 for n-hexane-water mixtures; Figure 10 Results diagrams of retention performance and flux test performance of the PLA@MOF composite membrane prepared in Example 1 and the PLA membrane prepared in Comparative Example 1 for cyclohexane oil-water mixtures; Figure 11 Results diagrams of retention performance and flux test performance of the PLA@MOF composite membrane prepared in Example 1 and the PLA membrane prepared in Comparative Example 1 for gasoline oil-water mixtures; Figure 12 Results diagrams of retention performance and flux test performance of the PLA@MOF composite membrane prepared in Example 1 and the PLA membrane prepared in Comparative Example 1 for soybean oil oil-water mixtures. Detailed implementation manners
[0044] The embodiments of the technical solutions of the present application will be described in detail below with reference to the accompanying drawings. The following embodiments are only used to illustrate the technical solutions of the present application more clearly, so they are only examples and cannot be used to limit the protection scope of the present application.
[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above accompanying drawings are intended to cover non-exclusive inclusion.
[0046] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly specifying the quantity, specific order or primary-secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "a plurality of" is more than two, unless otherwise specifically defined.
[0047] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in connection with the embodiments can be included in at least one embodiment of the present application. The phrase does not necessarily refer to the same embodiment at every occurrence in the specification, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art will explicitly and implicitly understand that the embodiments described herein can be combined with other embodiments.
[0048] The "scope" disclosed in the present application is defined in the form of a lower limit and an upper limit. A given scope is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of the particular scope. The scope defined in this way can include the end values or not include the end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a scope. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, ranges of 60-110 and 80-120 are also contemplated. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4, and 5 are listed, then the following ranges are all contemplated: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In the present application, unless otherwise specified, the numerical range "a-b" represents an abbreviated representation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "2-10" means that all real numbers between "2-10" have been fully listed herein, and "2-10" is only an abbreviated representation of these numerical combinations. Additionally, when stating that a certain parameter is an integer ≥2, it is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0049] In the description of the embodiments of the present application, the term "and / or" is merely a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: the existence of A, the simultaneous existence of A and B, and the existence of B. Additionally, the character " / " in this document generally represents an "or" relationship between the associated objects before and after.
[0050] The composite film and its preparation method in the present application will be further described below in conjunction with specific embodiments; the materials and reagents used in the following embodiments, unless otherwise specified, can all be commercially available products without limitation.
[0051] Example 1 This embodiment provides a method for preparing a composite membrane, as shown in the schematic diagram Figure 1 The preparation method includes the following steps: (1) Using a melting-type 3D printer, precise control of the membrane structure and size is achieved by layer-by-layer deposition of molten PLA filaments. The initial design of the PLA membrane model is completed using Siemens NX software, and the slicing operation is performed using Simplify3D software. Subsequently, the sliced model is imported into the 3D printer, and the molten thermoplastic filaments are extruded onto the printing platform through the fused deposition modeling technology (FDM technology) to form a strong and uniform membrane composed of two layers of intertwined filaments layer by layer; Specifically, the parameters involved in the fused deposition process are as follows: the extruder head temperature is 180 °C; the printer bed temperature is 70 °C; the layer height is 0.2 mm; the printing speed is 96 mm / s; the flow rate is 2.8 mm 3 / s; the diameter of the extruder head is 0.4 mm; the extrusion rate of the extruder head is 80%, and the extrusion magnification is 70%.
[0052] (2) The PLA membrane obtained in step (1) is immersed in a 10 g / L NaOH solution at 60 °C for soaking and etching for 30 min to roughen its surface.
[0053] (3) The NaOH-pretreated PLA membrane obtained in step (2) is rinsed with deionized water and reserved for use.
[0054] (4) Prepare the CoBDC-NH2 reaction solution. The specific method is as follows: A mixed solution composed of 0.9 g of cobalt(II) sulfate heptahydrate, 0.4 g of polyvinylpyrrolidone, 0.43 g of 2-aminoterephthalic acid, and 100 mL of methanol is ultrasonically treated for 5 min.
[0055] (5) The deionized water-rinsed NaOH-pretreated PLA membrane obtained in step (3) is placed in the reaction solution obtained in step (4) to allow in-situ growth of the PLA membrane for 48 h to obtain the composite membrane with a porosity of 20%, rectangular holes, and a pore size of 150 μm × 100 μm.
[0056] Example 2 (1) Using a melting-type 3D printer, precise control of the membrane structure and size is achieved by layer-by-layer deposition of molten PLA filaments. The initial design of the PLA membrane model is completed using Siemens NX software, and the slicing operation is performed using Simplify3D software. Subsequently, the sliced model is imported into the 3D printer, and the molten thermoplastic filaments are extruded onto the printing platform through the FDM technology to form a strong and uniform membrane composed of two layers of intertwined filaments layer by layer; Specifically, the parameters involved in the fused deposition process are as follows: the extruder head temperature is 180 °C; the printer bed temperature is 70 °C; the layer height is 0.2 mm; the printing speed is 96 mm / s; the flow rate is 2.8 mm 3 / s; the diameter of the extruder head is 0.4 mm; the extrusion rate of the extruder head is 90%, and the extrusion ratio is 70%.
[0057] (2) Immerse the PLA film obtained in step (1) in a 15 g / L NaOH solution at 50 °C for soaking and etching for 20 min to roughen its surface.
[0058] (3) Rinse the NaOH-pretreated PLA film obtained in step (2) with deionized water and set it aside for later use.
[0059] (4) Prepare the CoBDC-NH2 reaction solution. The specific method is as follows: Ultrasonically treat a mixed solution composed of 0.9 g of cobalt(II) sulfate heptahydrate, 0.4 g of polyvinylpyrrolidone, 0.43 g of 2-aminoterephthalic acid, and 100 mL of methanol for 6 min.
[0060] (5) Put the deionized water-rinsed NaOH-pretreated PLA film obtained in step (3) into the reaction solution obtained in step (4) to allow the PLA film to grow in-situ for 24 h to obtain the composite film with a porosity of 10%, the holes being rectangular with a pore size of 150 μm × 100 μm.
[0061] Example 3 (1) Use a fused deposition 3D printer to precisely control the membrane structure and size by layer-by-layer deposition of molten PLA filaments. The initial design of the PLA film model is completed using Siemens NX software, and the slicing operation is carried out through Simplify3D software. Subsequently, import the sliced model into the 3D printer and extrude the molten thermoplastic filaments onto the printing platform through FDM technology to form a strong and uniform film composed of two layers of intertwined filaments layer by layer; Specifically, the parameters involved in the fused deposition process are as follows: the extruder head temperature is 180 °C; the printer bed temperature is 70 °C; the layer height is 0.2 mm; the printing speed is 96 mm / s; the flow rate is 2.8 mm3 / s; the diameter of the extruder head is 0.4 mm; the extrusion rate of the extruder head is 70%, and the extrusion ratio is 70%.
[0062] (2) Immerse the PLA film obtained in step (1) in a 5 g / L NaOH solution at 70 °C for soaking and etching for 40 min to roughen its surface.
[0063] (3) Rinse the NaOH-pretreated PLA film obtained in step (2) with deionized water and set it aside for later use.
[0064] (4) Prepare the CoBDC-NH2 reaction solution. The specific method is as follows: A mixed solution composed of 0.9 g of cobalt(II) sulfate heptahydrate, 0.4 g of polyvinylpyrrolidone, 0.43 g of 2-aminoterephthalic acid, and 100 mL of methanol is ultrasonically treated for 5.5 min.
[0065] (5) Put the NaOH-pretreated PLA membrane rinsed with deionized water obtained in step (3) into the reaction solution obtained in step (4), and let the PLA membrane grow in situ for 50 h to obtain the composite membrane. The porosity is 30%, the holes are rectangular, and the pore size is 150 μm × 100 μm.
[0066] Examples 4 - 5 The difference between Examples 4 - 5 and Example 1 is that the concentration of the NaOH solution is different, which is 4 g / L (Example 4) and 16 g / L (Example 5) respectively, and the rest are the same as Example 1.
[0067] Examples 6 - 7 The difference between Examples 6 - 7 and Example 1 is that the soaking time in step (2) is different, which is 18 min (Example 6) and 42 min (Example 7) respectively, and the rest are the same as Example 1.
[0068] Examples 8 - 9 The difference between Examples 8 - 9 and Example 1 is that the mass ratio of 2-aminoterephthalic acid to cobalt(II) sulfate heptahydrate in step (4) is different, specifically as follows: Example 8: The addition amount of 2-aminoterephthalic acid is 0.43 g, and the addition amount of 0.9 g of cobalt(II) sulfate heptahydrate is 0.43 g. The mass ratio of the two is 1:1, and the rest are the same as Example 1.
[0069] Example 9: The addition amount of 2-aminoterephthalic acid is 0.43 g, and the addition amount of 0.9 g of cobalt(II) sulfate heptahydrate is 1.29 g. The mass ratio of the two is 1:3, and the rest are the same as Example 1.
[0070] Example 10 The difference between this example and Example 1 is that methanol is replaced with an equal volume of dimethylformamide, and the rest are the same as Example 1.
[0071] Example 11 The difference between this example and Example 1 is that 2-aminoterephthalic acid is replaced with an equal mass of terephthalic acid, and the rest are the same as Example 1.
[0072] Example 12 The difference between this example and Example 1 is that cobalt(II) sulfate heptahydrate is replaced with an equal mass of cobalt nitrate, and the rest is the same as in Example 1.
[0073] Comparative Example 1 The difference between this comparative example and Example 1 is that steps (2), (4), and (5) are not included, and the rest is the same as in Example 1.
[0074] Comparative Example 2 The difference between this comparative example and Example 1 is that step (2) is not included, and the rest is the same as in Example 1.
[0075] Performance Test (1) Surface Morphology: Taking Example 1 and Comparative Example 1 as examples, the obtained films were respectively analyzed for their morphology using a scanning electron microscope, and the results are as Figure 2 and Figure 3 shown. Compared with Comparative Example 1, the surface of Example 1 is rough, and there are many flaky objects. These flaky objects are the metal-organic framework CoBDC-NH2.
[0076] (2) Wettability: Wettability is reflected by the water contact angle. The water contact angle is measured using a contact angle measuring instrument from Konow Co., Ltd., USA. The composite film is pasted on a glass slide using double-sided tape, and then measured using the contact angle measuring instrument.
[0077] Taking Example 1 and Comparative Example 1 as examples, the results are as Figure 4 shown. For the PLA film after in-situ growth of MOF (PLA@MOF film) in Example 1 compared with the original PLA film in Comparative Example 1, its water contact angle has decreased significantly, from 106.83° of the original PLA film to 20.53°, proving that the hydrophilicity of the PLA@MOF film after in-situ growth of MOF has been improved, that is, the composite film obtained by the preparation method described in this application has better hydrophilicity.
[0078] (3) Determination of Test Pore Size: Taking the composite film of Example 1 and the PLA film of Comparative Example 1 for separation performance testing, and applying them to the filtration separation of n-hexane oil-water mixture to select the optimal pore size.
[0079] Specifically, composite films with different pore sizes are prepared in a similar method by adjusting the extrusion ratio in step (1); The extrusion ratio for a pore size of 150 μm × 100 μm is 80%; The extrusion ratio for a pore size of 250 μm × 220 μm is 70%; The extrusion ratio for a pore size of 200 μm × 180 μm is 60%.
[0080] The results are asFigure 5 and Figure 6 As shown in Figure 6 , the rejection rates of the three different pore-sized PLA membranes in Comparative Example 1 for the n-hexane oil-water mixture were all lower than 3%. Among the three different pore-sized PLA@MOF composite membranes in Example 1, the rejection rates were not good for those with pore sizes of 250 μm×220 μm and 200 μm×180 μm, while the PLA@MOF composite membrane with a pore size of 150 μm×100 μm showed a separation efficiency of 99.7%.
[0081] Therefore, subsequent tests were all carried out using a pore size of 150 μm×100 μm.
[0082] (4) Rejection performance of the oil-water mixture: The composite membrane was integrated into a tubular device with an effective separation area of 1.78 cm². In the experiment, the oil phase and the water phase were mixed at a volume ratio of 1:1. The oil phase was dyed red with Oil Red O, and the water phase was dyed blue with Coomassie Brilliant Blue. Throughout the experiment, the separation was driven only by gravity without using any pressurization equipment. The separation efficiency was evaluated by the following formula (1): Separation efficiency (%) = (1) In formula (1), m1 and m0 represent the weight of the permeated oil and the oil before separation, respectively.
[0083] The oil permeation flux J (L·m -2 ·h -1 ) can be calculated according to formula (2): (2) Where V, A, and T represent the volume of the permeated oil (L), the effective membrane area (m 2 ), and the permeation time (h), respectively.
[0084] Taking the example of the examples, the results are as Figures 7 - 12 shown. The separation performance tests of six different oil-water mixtures were carried out; the composite membrane showed a separation efficiency higher than 99.2% and a flux of 2.88 × 10 5 L·m -2 ·h -1 for all six different oil-water mixtures.
[0085] Therefore, the composite membrane obtained by the preparation method described in this application has at least high permeability and excellent separation performance for oil-water mixtures.
[0086] The separation efficiencies and fluxes of petroleum ether for each example and comparative example were summarized in Table 1.
[0087] Table 1
[0088] Analysis of Comparative Examples 1-2 and Example 1 shows that the performance of Comparative Examples 1-2 is inferior to that of Example 1, proving that the composite film obtained by the preparation method described in this application has better performance.
[0089] Analysis of Examples 4-5 and Example 1 shows that the performance of Examples 4-5 is inferior to that of Example 1, proving that the composite film prepared with the alkali solution concentration in the range of 5-15 g / L has better performance. Among them, the composite film of Example 5 was ruptured and the data was not tested.
[0090] Analysis of Examples 6-7 and Example 1 shows that the performance of Examples 6-7 is inferior to that of Example 1, proving that the composite film prepared with the alkali solution soaking time in the range of 20-40 min has better performance. Among them, the composite film of Example 7 was ruptured and the data was not tested.
[0091] Analysis of Examples 8-9 and Example 1 shows that the performance of Examples 8-9 is inferior to that of Example 1, proving that the composite film prepared with the mass ratio of 2-aminoterephthalic acid to cobalt metal salt in the range of 1:(1.5-2.5) has better performance.
[0092] Analysis of Examples 10-12 and Example 1 shows that the performance of Examples 10-12 is inferior to that of Example 1, proving that the composite film prepared with 2-aminoterephthalic acid, cobalt metal salt and methanol as the raw materials of the metal-organic framework reaction solution has better performance.
[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions recorded in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be covered by the scope of the claims and the description of the present application. In particular, as long as there is no structural conflict, the technical features mentioned in each embodiment can be combined in any way. The present application is not limited to the specific embodiments disclosed in the text, but includes all technical solutions falling within the scope of the claims.
Claims
1. A method for preparing a composite film, characterized in that, The preparation method includes the following steps: After soaking the polylactic acid film in an alkaline solution, it is then placed in a metal-organic framework reaction solution for in-situ growth to obtain the composite film.
2. The preparation method according to claim 1, characterized in that, The concentration of the alkaline solution is 5 - 15 g / L; and / or; The alkali in the alkaline solution includes sodium hydroxide.
3. The preparation method according to claim 1, characterized in that, The temperature of the soaking is 50 - 70 °C; and / or; The time of the soaking is 20 - 40 min.
4. The preparation method according to claim 1, characterized in that, After the soaking, the operation of washing the polylactic acid film is also included.
5. The preparation method according to claim 1, characterized in that, The raw materials for preparing the metal-organic framework reaction solution include 2-aminoterephthalic acid, a cobalt-based metal salt, and methanol; and / or; The mass ratio of 2-aminoterephthalic acid to the cobalt-based metal salt is 1:(1.5 - 2.5).
6. The preparation method according to claim 1, characterized in that, The preparation method of the metal-organic framework reaction solution includes: mixing 2-aminoterephthalic acid, a cobalt-based metal salt, and methanol, and performing ultrasonic treatment to obtain the metal-organic framework reaction solution; and / or; The time of the ultrasonic treatment is 5 - 6 min.
7. The preparation method according to claim 1, characterized in that, The time of the in-situ growth is 24 - 50 h.
8. The preparation method according to claim 1, characterized in that, The preparation method includes the following steps: (1) Mix 2-aminoterephthalic acid and a cobalt-based metal salt with methanol, and perform ultrasonic treatment for 5 - 6 min to obtain a metal-organic framework reaction solution; The mass ratio of 2-aminoterephthalic acid to the cobalt-based metal salt is 1:(1.5 - 2.5); Soak the polylactic acid film in an alkaline solution with a concentration of 5 - 15 g / at 50 - 70 °C for 20 - 40 min, and wash; (2) Place the polylactic acid film in the metal-organic framework reaction solution for in-situ growth for 24 - 50 h to obtain the composite film.
9. A composite film, characterized in that, The composite film is obtained by the preparation method according to any one of claims 1 - 8; The composite film includes pores, and the diameter of the circumscribed circle of the pores is 100 - 250 μm; and / or; The porosity of the composite film is 10% - 30%.
10. Application of the composite film according to claim 9 in water purification.
Citation Information
Patent Citations
Polyvinylidene fluoride and metal-organic framework composite ultra-filtration membrane and preparation and application
CN105498553A
Preparation method of highly-anti-fouling polyvinylidene fluoride (PVDF) porous base composite ultrafiltration membrane material
CN110280150A
Multifunctional bio-based composite microporous membrane and preparation method thereof
CN111346523A
ZIF-8 polylactic acid composite filter membrane and preparation method thereof
CN117225207A
Super-hydrophobic metal organic framework composite material as well as preparation method and application thereof
CN119219927A